Calogênese in vitro como alternativa na produção de metabólitos secundários e comparação metabólica entre calos e plantas de Artemisia annua - Iiyama, Carla Midori (Universidade Federal de São Carlos, 2023)
Among the applications of in vitro culture technique of medicinal plants are the use of clonal plantlets from previously selected superior genotypes, the production of metabolites in controlled environment and genetic transformation aiming at the production of specific tissues and metabolites. The in vitro production of secondary metabolites has the advantage of a controlled environment, free of pests and pathogens, in addition to allowing the production of metabolic profile different from those produced in cultivated plants. The present work aimed to establish a protocol for in vitro calli induction and proliferation of the medicinal plant Artemisia annua and to compare the metabolic profile of calli with in vitro plantlets and plants grown in a greenhouse. In addition, the effects of wavelengths of the visible light spectrum (dark, white, blue, red, blue and red) on the production of secondary metabolites were evaluated. The presence of phytoregulators Benzylaminopurine (BAP) and Naphthalene Acetic Acid (NAA) at 1.0 mg L-1 each, promoted the induction and proliferation of calli, with an increase in diameter and fresh weight. SPME GC-MS analyzes showed differences in the metabolic profile produced in different cultivation systems of A. annua and wavelengths used in calli cultivation. White light (cold and fluorescent) and red light (LEDs) resulted in a greater diversity of metabolites produced in calli, with six metabolites found exclusively in calli cultivated under red light, demonstrating specificity of calli response. 27 metabolites were identified exclusively in the calli of A. annua and four of them were reported for the first time in the species: menthyl acetate, geranyl acetate, 4-methoxy benzaldehyde and alpha-santalene. The results demonstrate the potential of in vitro culture of A. annua calli in the production of metabolites different from those obtained in different tissues, such as in vitro plantlets and plants grown in greenhouse.
In vitro callogenesis as an alternative in the production of secondary metabolites and metabolic comparison between callus and plants of Artemisia annua
Keywords: Artemisia annua; Planta medicinal; Medicinal plant; Calogênese; Callogenesis; Micropropagação; Micropropagation; Metabólitos secundários; Secondary metabolites; CIENCIAS AGRARIAS